Preparation process of high-performance concrete and application of high-performance concrete in building structure

By adjusting the proportion of components in high-performance concrete, especially increasing the use of fiber materials and shrinkage agents, the problems of increasing self-shrinkage and cracks in the production process are solved, and concrete preparation with high compression, flexural and crack resistance are achieved, improving the safety of building structures.

CN119661152AActive Publication Date: 2025-03-21SHENZHEN ZHONGTIANYUAN IND CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411838881.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

During the production process, high-performance concrete increases the degree of self-shrinkage due to the increase in hydration heat and the increase in the amount of gelling materials, which easily leads to cracks, affecting the safety of the building structure.

Method used

Concrete with good compressive strength, flexural strength and crack resistance is prepared by adjusting the proportion of components in high-performance concrete, including cement, fly ash, slag powder, fiber materials and shrinkage agents.

Benefits of technology

The prepared high-performance concrete has good compressive strength, flexural strength and crack resistance, which reduces the generation of cracks and improves the safety and service life of the building structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005187472010000051
    Figure BDA0005187472010000051
  • Figure BDA0005187472010000062
    Figure BDA0005187472010000062
  • Figure BDA0005187472010000063
    Figure BDA0005187472010000063
Patent Text Reader

Abstract

The invention discloses a preparation process of high-performance concrete and application of the high-performance concrete in a building structure. The high-performance concrete is prepared from the following components in parts by weight: 330 to 350 parts of cement, 70 to 80 parts of fly ash, 90 to 100 parts of slag powder, 2 to 3 parts of a water reducing agent, 550 to 600 parts of fine aggregate, 850 to 900 parts of coarse aggregate, 20 to 50 parts of a fiber material, 20 to 30 parts of a shrinkage reducing agent and 160 to 180 parts of water. By adjusting the proportion of all the components in the high-performance concrete, the prepared concrete has good compressive strength and breaking strength, cracks are not prone to being generated, and the application of the concrete in building structures is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a preparation process of high-performance concrete and application thereof in building structures. Background Art

[0002] High-performance concrete is a new type of high-tech concrete, produced with conventional materials and processes, with various mechanical properties required by concrete structures, and with high durability, high workability and high volume stability. High-performance concrete is mainly used in highways, bridges, high-rise buildings, underground engineering and other fields. With the development of construction technology, large, super-large, high-rise and super-high-rise buildings have put forward higher requirements on the performance of concrete.

[0003] In practical applications, high-performance concrete uses a large amount of cement. The increase in the amount of cementitious materials will lead to an increase in the hydration heat of concrete, which will increase the degree of concrete shrinkage and easily cause cracks, which is very detrimental to the safety of building structures. The main components of high-performance concrete include water, cement, aggregates and admixtures. There are very strict requirements on the selection and proportion of materials during preparation. The addition of admixtures also has a great impact on high-performance concrete. The standardization of these technologies, to a certain extent, determines the promotion and use of high-performance concrete technology in practical applications. Therefore, it is particularly important to regulate the proportion of each component in high-performance concrete and the type and amount of admixtures added. Summary of the invention

[0004] Based on the problems existing in the background technology, the present invention provides a high-performance concrete. By adjusting the proportion of each component in the high-performance concrete, the prepared concrete has good compressive strength, flexural strength, and is not prone to cracks, thereby expanding its application in building structures.

[0005] The present invention is implemented by the following technical solutions:

[0006] On the one hand, the present invention discloses a high-performance concrete, which comprises the following components by weight: 330-350 parts of cement, 70-80 parts of fly ash, 90-100 parts of slag powder, 2-3 parts of water reducer, 550-600 parts of fine aggregate, 850-900 parts of coarse aggregate, 20-50 parts of fiber material, 20-30 parts of shrinkage reducer and 160-180 parts of water.

[0007] Furthermore, the cement is one or more of silicate cement, aluminate cement, and sulphoaluminate cement.

[0008] Furthermore, the water reducer is a polycarboxylic acid high performance water reducer.

[0009] Furthermore, the fine aggregate is a mixture of river sand and machine-made sand, and the weight ratio of river sand to machine-made sand is (2-3):1;

[0010] The fineness modulus of river sand is 2.5-2.9, and the mud content is less than 1%;

[0011] The fineness modulus of artificial sand is 2.7-3.0, and the mud content is less than 1%.

[0012] The coarse aggregate is one or both of crushed stone and pebbles, with a particle size range of 5-25 mm, a crushing index of less than 5%, and a needle-like particle content of less than 8%.

[0013] Furthermore, the fiber material is a mixture of surface-modified polyvinyl alcohol fiber and surface-modified basalt fiber, and the mass ratio of the surface-modified polyvinyl alcohol fiber to the surface-modified basalt fiber is (2-3):1.

[0014] Furthermore, the preparation steps of the surface-modified polyvinyl alcohol fiber are specifically as follows: treating the polyvinyl alcohol fiber in a dilute acetic acid solution with a mass concentration of 1-2% for 30-60 minutes, washing with water until neutral, and drying to obtain pretreated polyvinyl alcohol fiber; adding 10-15 parts of isophorone diisocyanate, 5-8 parts of KH550 silane coupling agent, and 3-5 parts of hydroxy acrylate to 100 parts of N-methylpyrrolidone by weight, and then adding 1-2 parts of dibutyltin dibutyrate, reacting at 60-80° C. for 3-4 hours under nitrogen protection, after the reaction is completed, adding the pretreated polyvinyl alcohol fiber to the reaction system, keeping the reaction temperature unchanged, stirring at 80-100 rpm for 1-2 hours, washing with ethanol after the reaction is completed, and drying in an environment of 60-70° C. to obtain the surface-modified polyvinyl alcohol fiber;

[0015] The diameter of the polyvinyl alcohol fiber is 30-50 μm and the length is 18 mm.

[0016] Furthermore, the preparation steps of the surface-modified basalt fiber are specifically as follows: preparing a surface treatment agent: dissolving 1-1.5 parts of KH550 silane coupling agent in 100 parts of water by weight, adding 2-2.6 parts of triethyl citrate, stirring evenly, continuing to add zinc oxide and silicon dioxide, the weight ratio of zinc oxide to silicon dioxide is 3:1, and the total amount of zinc oxide and silicon dioxide is 1-2.2 parts, ultrasonically dispersing to obtain a suspension, and adjusting the pH value of the suspension to 4-5 with diluted acetic acid to obtain a surface treatment agent; immersing the basalt fiber in the surface treatment agent, at a temperature of 60-70°C and a stirring speed of 80-100 rpm, immersing for 30-60 minutes, taking out the treated basalt fiber, and drying it in an environment of 120-130°C to obtain a surface-modified basalt fiber;

[0017] Among them, the diameter of basalt fiber is 9-17μm and the length is 5-15mm.

[0018] Furthermore, the shrinkage reducing agent is obtained by free radical copolymerization of an unsaturated polyether macromonomer and an acrylic acid aqueous solution.

[0019] The second aspect of the present invention discloses a process for preparing high performance concrete, comprising the following steps:

[0020] S1. Add cement, fly ash, slag powder, and fiber material to a mixer and mix well. Add fine aggregate and coarse aggregate and continue mixing to obtain a mixture.

[0021] S2: adding the water reducing agent into water and mixing evenly, then adding the water reducing agent into the mixture together with the shrinkage reducing agent, stirring evenly, to obtain the high performance concrete.

[0022] The third aspect of the present invention discloses the application of high performance concrete in building structures.

[0023] Beneficial effects of the present invention:

[0024] 1. The present invention adjusts the proportion of each component in high-performance concrete to prepare concrete with good compressive strength, flexural strength, and is not prone to cracks, thereby expanding its application in building structures.

[0025] 2. The fiber materials used in the present invention are surface-modified polyvinyl alcohol fiber and surface-modified basalt fiber. Isocyanate groups are introduced into surface-modified polyvinyl alcohol fiber. Isocyanate groups are highly active functional groups that can react with hydroxyl groups on the fiber surface to form urea bonds. The polarity and hydrogen bonding of urea bonds enhance the bonding force between the fiber and the matrix, and the urea bonds are not easily destroyed by alkaline solutions, so that the fiber can also maintain stability under high alkaline conditions. In addition, the cyclic structure of the isocyanate group provides a certain molecular flexibility, which helps to relieve stress concentration, thereby improving the toughness of concrete. The introduction of silane coupling agents can form stable siloxane bonds with the cement matrix to further enhance the interfacial bonding between the fiber and the matrix, and give the fiber higher durability. The silane coupling agent in the surface-modified basalt fiber is bonded to the Si-OH bond on the surface of the basalt fiber to form a stable chemical bond, and the organic functional group at the other end reacts with the calcium ions in the cement matrix to form a strong interfacial bond. The dual effects of chemical bonds and physical anchoring significantly enhance the bonding force between the fiber and the cement matrix. Triethyl citrate forms a flexible film on the fiber surface, improving the dispersion and tensile properties of the fiber; zinc oxide provides alkali resistance and antibacterial properties, extending the service life of the fiber in concrete; silicon dioxide particles enhance the surface roughness of the fiber and increase the mechanical bite of the fiber and the concrete matrix. The modified basalt fiber can be evenly distributed in the concrete, effectively improving the crack resistance, compressive strength and toughness of the concrete.

[0026] 3. The present invention uses fiber materials and shrinkage reducers to work together to further improve the crack resistance and shrinkage resistance of concrete; the use of polyvinyl alcohol fiber and basalt fiber in combination can not only improve the crack resistance and shrinkage resistance but also compensate for the reduction in concrete strength caused by the shrinkage reducer.

[0027] 4. Compared with polyether-type shrinkage-reducing agents, the shrinkage-reducing agent obtained by free radical copolymerization of unsaturated polyether macromonomer and acrylic acid aqueous solution is selected in the present invention, and the prepared concrete has better performance in combination with the other components of the concrete of the present invention. At the same time, the present invention avoids the problem that the water-reducing agent is not as good as the single-addition of the shrinkage-reducing agent. It is found through experiments that an appropriate amount of water-reducing agent is beneficial to improving the various properties of concrete. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following embodiments.

[0029] The raw materials used in the examples and comparative examples of the present invention are as follows:

[0030] The cement is P·O52.5 grade silicate cement; the fly ash is grade I fly ash; the slag powder is grade S95; the water reducer is a polycarboxylic acid high-performance water reducer; the river sand is medium-coarse natural river sand with a fineness modulus of 2.7 and a mud content of less than 1%; the machine-made sand is sealed machine-made sand with a fineness modulus of 2.9 and a mud content of less than 1%; the coarse aggregate is granite crushed stone with a particle size range of 5-25mm and a needle-like particle content of 7.1%; the polyvinyl alcohol fiber has a diameter of 30μm and a length of 18mm; the basalt fiber has a diameter of 12μm and a length of 8mm; the shrinkage reducer is obtained by free radical copolymerization of an unsaturated polyether macromonomer and an acrylic acid aqueous solution, and is purchased from the SRA2 shrinkage reducer developed by Jiangsu Subote New Materials Co., Ltd. The shrinkage reducer has a solid content of 35%, a pH value of 7±1, and a density of 1.05±0.02g / cm 3 .

[0031] The preparation steps of the surface-modified polyvinyl alcohol fiber are specifically as follows: treating the polyvinyl alcohol fiber in a dilute acetic acid solution with a mass concentration of 1.5% for 45 minutes, washing with water until neutral, and drying to obtain pretreated polyvinyl alcohol fiber; adding 12 parts of isophorone diisocyanate, 6 parts of KH550 silane coupling agent, and 4 parts of hydroxy acrylate to 100 parts of N-methylpyrrolidone by weight, and then adding 1.5 parts of dibutyltin dibutyrate, reacting at 70°C for 3 hours under nitrogen protection, and after the reaction is completed, adding the pretreated polyvinyl alcohol fiber to the reaction system, keeping the reaction temperature unchanged, stirring at 100 rpm for 1 hour, washing with ethanol after the reaction is completed, and drying in an environment of 60°C to obtain the surface-modified polyvinyl alcohol fiber.

[0032] The preparation steps of the surface-modified basalt fiber are as follows: prepare the surface treatment agent: dissolve 1.3 parts of KH550 silane coupling agent in 100 parts of water by weight, add 2.2 parts of triethyl citrate, stir evenly, continue to add zinc oxide and silicon dioxide, the weight ratio of zinc oxide to silicon dioxide is 3:1, the total amount of zinc oxide and silicon dioxide is 1.6 parts, ultrasonically disperse to obtain a suspension, adjust the pH value of the suspension to 4.5 with diluted acetic acid, and obtain the surface treatment agent; immerse the basalt fiber in the surface treatment agent, immerse for 30 minutes at a temperature of 70°C and a stirring speed of 100 rpm, take out the treated basalt fiber, and dry it in an environment of 120°C to obtain the surface-modified basalt fiber;

[0033] The raw material dosage ratios for preparing high performance concrete in the embodiments of the present invention and the comparative examples are shown in Tables 1-3, wherein the added amounts are all in parts by weight.

[0034] Table 1

[0035]

[0036]

[0037] Table 2

[0038]

[0039] Table 3

[0040]

[0041]

[0042] The shrinkage reducing agent of Comparative Example 12 in Table 2 is a polyether shrinkage reducing agent.

[0043] Example 6

[0044] A preparation process of high performance concrete comprises the following steps:

[0045] S1. Add cement, fly ash, slag powder, and fiber material to a mixer and mix well. Add fine aggregate and coarse aggregate and continue mixing to obtain a mixture.

[0046] S2: adding the water reducing agent into water and mixing evenly, then adding the water reducing agent into the mixture together with the shrinkage reducing agent, stirring evenly, to obtain the high performance concrete.

[0047] Test example

[0048] High performance concrete was prepared using the formulations of Examples 1-5 and Comparative Examples 1-12 and the preparation method of Example 6, and the performance of the concrete was tested using the following method.

[0049] 1. Compressive strength test

[0050] Standard test blocks were made in accordance with GB / T50081-2019 "Standard Test Method for Mechanical Properties of Ordinary Concrete", and the compressive strength of the standard test blocks was measured after 28 days of curing.

[0051] 2. Flexural strength test

[0052] Standard test blocks were made in accordance with GB / T50081-2019 "Standard Test Method for Mechanical Properties of Ordinary Concrete", and the flexural strength of the standard test blocks was measured after 28 days of curing.

[0053] 3. Early crack resistance

[0054] According to GB / T50081-2019 "Standard Test Method for Mechanical Properties of Ordinary Concrete", standard test blocks are made, and the number of cracks per unit area measured 24 hours after concrete pouring is calculated and recorded as the number of cracks.

[0055] 4. Shrinkage test

[0056] Standard test blocks were made in accordance with GB / T50081-2019 "Standard Test Methods for Mechanical Properties of Ordinary Concrete", cured in an outdoor environment at 40°C, and then referenced GB / T50082-2009 "Standard Test Methods for Long-term Performance and Durability of Ordinary Concrete" to record the 28d shrinkage data.

[0057] The specific test results are shown in Table 4.

[0058] Table 4

[0059]

[0060]

[0061] It can be seen from the results in Table 4 that the concrete prepared in Examples 1-5 of the present invention has higher compressive strength, flexural strength and lower shrinkage, and excellent crack resistance.

[0062] In Comparative Example 1, no fiber material was added, and it was found that various properties of the concrete were significantly reduced; in Comparative Example 2, only surface-modified polyvinyl alcohol fiber was added, and in Comparative Example 3, only surface-modified basalt fiber was added. From the data in Table 4, it can be seen that after the addition of surface-modified polyvinyl alcohol fiber in Comparative Example 2, its crack resistance and shrinkage are better than those in Comparative Example 3, but after the addition of surface-modified basalt fiber in Comparative Example 3, its compressive strength is better than that in Comparative Example 2; in Comparative Example 4, unmodified polyvinyl alcohol fiber and unmodified basalt fiber were added at the same time. Compared with Example 1, the compressive strength of the concrete is reduced, the shrinkage rate is increased, and the crack resistance is reduced.

[0063] In Comparative Example 5, no water reducer was added, and the fluidity of the concrete decreased, resulting in a significant decrease in the compressive strength; in Comparative Example 6, the amount of water reducer was increased, and the compressive strength and crack resistance of the concrete decreased, which may be because the amount of water reducer increased and the porosity increased, resulting in a decrease in performance; in Comparative Example 7, the amount of water reducer was reduced, and the compressive strength of the concrete was improved compared with that in Comparative Example 5, but it was significantly lower than that in Example 1, indicating that the addition of water reducer is beneficial to improving the various properties of concrete, but the amount is not much, and the performance improvement is not obvious.

[0064] In Comparative Example 8, no shrinkage-reducing agent was added, and the crack resistance and shrinkage resistance of the prepared concrete were the worst in this group of experiments; in Comparative Example 9, a small amount of shrinkage-reducing agent was added, and the crack resistance and shrinkage resistance were also improved, but the expected effect was not achieved.

[0065] In Comparative Example 10, no slag powder was added, and the crack resistance and shrinkage resistance of the concrete decreased. Increasing the amount of fly ash will increase the drying shrinkage. The addition of slag powder can optimize the pore structure of the concrete.

[0066] In Comparative Example 11, the amount of machine-made sand was increased and the amount of river sand was reduced. It was found that all properties of the concrete decreased. The machine-made sand became irregular after crushing and had poor fluidity. Adding more sand would affect the performance of the concrete.

[0067] In Comparative Example 12, a polyether type shrinkage-reducing agent was used, and it was found that various properties of the concrete prepared with the polyether type shrinkage-reducing agent were lower than those of the concrete prepared with the shrinkage-reducing agent obtained by free radical copolymerization of an unsaturated polyether macromonomer and an aqueous acrylic acid solution according to the present invention.

[0068] Finally, it should be noted that the above-mentioned embodiments only express several implementation methods of the present invention and are not intended to limit the invention. For those skilled in the art, any modification, equivalent replacement, improvement, etc. made without departing from the concept of the present invention should be included in the protection scope of the invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A high performance concrete, characterized in that: The present invention comprises the following components by weight: 330-350 parts of cement, 70-80 parts of fly ash, 90-100 parts of slag powder, 2-3 parts of water reducing agent, 550-600 parts of fine aggregate, 850-900 parts of coarse aggregate, 20-50 parts of fiber material, 20-30 parts of shrinkage reducing agent and 160-180 parts of water.

2. The high performance concrete according to claim 1, characterized in that: The cement is one or more of silicate cement, aluminate cement and sulphoaluminate cement.

3. The high performance concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid high performance water reducing agent.

4. The high performance concrete according to claim 1, characterized in that: The fine aggregate is a mixture of river sand and machine-made sand, and the weight ratio of river sand to machine-made sand is (2-3):1; The fineness modulus of river sand is 2.5-2.9, and the mud content is less than 1%; The fineness modulus of machine-made sand is 2.7-3.0, and the mud content is less than 1%; The coarse aggregate is one or both of crushed stone and pebbles, with a particle size range of 5-25 mm, a crushing index of less than 5%, and a needle-like particle content of less than 8%.

5. The high performance concrete according to claim 1, characterized in that: The fiber material is a mixture of surface-modified polyvinyl alcohol fiber and surface-modified basalt fiber, and the mass ratio of the surface-modified polyvinyl alcohol fiber to the surface-modified basalt fiber is (2-3):

1.

6. The high performance concrete according to claim 5, characterized in that: The preparation steps of the surface-modified polyvinyl alcohol fiber are as follows: treating the polyvinyl alcohol fiber in a dilute acetic acid solution with a mass concentration of 1-2% for 30-60 minutes, washing with water until neutral, and drying to obtain pretreated polyvinyl alcohol fiber; In parts by weight, 10-15 parts of isophorone diisocyanate, 5-8 parts of KH550 silane coupling agent, and 3-5 parts of hydroxy acrylate are added to 100 parts of N-methylpyrrolidone, and 1-2 parts of dibutyltin dibutyrate are added, and the reaction is carried out at 60-80° C. for 3-4 hours under nitrogen protection. After the reaction is completed, the pretreated polyvinyl alcohol fiber is added to the reaction system, the reaction temperature is kept unchanged, and the stirring is continued at 80-100 rpm for 1-2 hours. After the reaction is completed, the fiber is washed with ethanol and dried in an environment of 60-70° C. to obtain the surface-modified polyvinyl alcohol fiber; The diameter of the polyvinyl alcohol fiber is 30-50 μm and the length is 18 mm.

7. The high performance concrete according to claim 5, characterized in that: The preparation steps of the surface-modified basalt fiber are specifically as follows: preparing a surface treatment agent: dissolving 1-1.5 parts of KH550 silane coupling agent in 100 parts of water by weight, adding 2-2.6 parts of triethyl citrate, stirring evenly, continuing to add zinc oxide and silicon dioxide, the weight ratio of zinc oxide to silicon dioxide is 3:1, and the total amount of zinc oxide and silicon dioxide is 1-2.2 parts, ultrasonically dispersing to obtain a suspension, and adjusting the pH value of the suspension to 4-5 with diluted acetic acid to obtain the surface treatment agent; immersing the basalt fiber in the surface treatment agent, at a temperature of 60-70°C and a stirring speed of 80-100 rpm, immersing for 30-60 minutes, taking out the treated basalt fiber, and drying it in an environment of 120-130°C to obtain the surface-modified basalt fiber; Among them, the diameter of basalt fiber is 9-17μm and the length is 5-15mm.

8. The high performance concrete according to claim 1, characterized in that: The shrinkage reducing agent is obtained by free radical copolymerization of unsaturated polyether macromonomer and acrylic acid aqueous solution.

9. A process for preparing high performance concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Add cement, fly ash, slag powder, and fiber material to a mixer and mix well. Add fine aggregate and coarse aggregate and continue mixing to obtain a mixture. S2: adding the water reducing agent into water and mixing evenly, then adding the water reducing agent into the mixture together with the shrinkage reducing agent, stirring evenly, to obtain the high performance concrete.

10. Use of the high performance concrete according to any one of claims 1 to 9 in a building structure.

Citation Information

Patent Citations

  • High-performance concrete and preparation method thereof

    CN106517920A

  • High-performance fiber concrete and preparation method thereof

    CN112960949A

  • Basalt-polyvinyl alcohol hybrid fiber reinforced cement concrete and preparation method thereof

    CN115677296A

  • High-density counterweight anti-crack concrete and preparation method thereof

    CN116621520A

  • Building material containing waste and preparation method thereof

    CN118908687A